School Absence Seen from a School Perspective and a Parent Perspective - Klaus Nielsen; Mikael Thastum (Nordic Studies in Education, 2023)
Inspired by social practice theory (Lave & Wenger, 1991; Nielsen, 2016), this article adopts a contextual perspective to address school absence, specifically focusing on the relationship between parents and schools in addressing excessive school absence. The central questions of the article are: How do parents of children with excessive school absence perceive the support they receive from the school? Secondly, why do schools struggle to support parents dealing with children with excessive school absence? By exploring the experiences of parents and school staff in their interactions regarding excessive school absence, the article highlights how the organization of everyday practices influences the dynamics between schools and parents. The study is based on 41 interviews, including 24 interviews with parents, four with school leaders, four with pedagogical leaders, and 11 with teachers. The article reveals that parents of children with excessive absence describe feeling left in a communicative vacuum due to schools not taking sufficient action regarding their children’s absences. On the other hand, school staff reported challenges related to internal coordination, negotiation of responsibilities, and limited resources in implementing long-term systematic interventions for parents dealing with children with excessive school absence. The article argues that in order to understand and address school absence effectively, it is essential to consider its contextual and relational nature.